Beckman Electrolyte 2 Analyzer (1980)
Beckman's Electrolyte 2 Analyzer debuted in 1980.
Keywords: Medical laboratory technology; Medical electronics--Equipment and supplies; Scientific apparatus and instruments; Electrolytes; Electrolytes--Analysis; Beckman Instruments, Inc.